Chapter Føllesdal and Frege on Reference - Linnebo, Øystein (De Gruyter, 2013)
In this essay I first identify some desiderata for a theory of reference that appear in Føllesdal's later work (Section 1). We will see that these desiderata are highly Fregean in character. Next I outline a Frege-inspired theory of (a certain core form of) reference that I have been developing in my own work (Section 2). Finally I argue that this theory (as far as it goes) satisfies Føllesdal's desiderata (Section 3). In particular, I argue that, when the distinction between semantics proper and the theory of reference is carefully heeded, my Frege-inspired theory of reference can be seen to be fully compatible with Føllesdal's "two-sorted semantics." The Fregeanism that I advocate is thus highly selective: its only direct concern is the theory of reference, not semantics proper.